2019
DOI: 10.1080/16549716.2018.1480085
|View full text |Cite
|
Sign up to set email alerts
|

An invisible workforce: the neglected role of cleaners in patient safety on maternity units

Abstract: Hospital cleaning has been shown to impact on rates of healthcare-associated infections (HCAIs) and good environmental hygiene is critical to quality care, yet those tasked with the role of ensuring a safe and clean environment often go unrecognised as members of the healthcare workforce. Sepsis is a leading cause of maternal and newborn death, a significant proportion of these cases are estimated to be due to HCAIs. Deliveries in health institutions have now reached 75% globally, and in low and middle income … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
57
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(57 citation statements)
references
References 23 publications
0
57
0
Order By: Relevance
“…Ours is the rst study to evaluate the potential of environmental cleaning as a standalone HAI prevention intervention, with only one prior study including cleaning in a neonatal infection prevention bundle. 20 Furthermore, the key contribution of hospital cleaners and cleaning practices to patient safety is underappreciated in many LMIC settings 24 , despite the substantial risk of pathogen transmission from environmental reservoirs. [4][5][6] In this paper, we report the impact of a multimodal intervention (neoCLEAN) on the adequacy of surface and equipment cleaning in a South African neonatal ward using bacterial cultures, ATP assays and UV marker removal rates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ours is the rst study to evaluate the potential of environmental cleaning as a standalone HAI prevention intervention, with only one prior study including cleaning in a neonatal infection prevention bundle. 20 Furthermore, the key contribution of hospital cleaners and cleaning practices to patient safety is underappreciated in many LMIC settings 24 , despite the substantial risk of pathogen transmission from environmental reservoirs. [4][5][6] In this paper, we report the impact of a multimodal intervention (neoCLEAN) on the adequacy of surface and equipment cleaning in a South African neonatal ward using bacterial cultures, ATP assays and UV marker removal rates.…”
Section: Discussionmentioning
confidence: 99%
“…27 Prior studies of hospital cleaning in resource-limited settings identi ed lack of training, low societal value attached to cleaning, and disempowerment of cleaning staff, as major factors that perpetuate poor cleaning performance. 5,24 In a survey of healthcare facilities in India, Bangladesh, The Gambia and Zanzibar 24 , few gave formal training to their cleaning staff and the role of cleaning was generally not perceived as important. As African obstetric and neonatal units strive to attain the Sustainable Development Goals for maternal and newborn health and survival and reduce the spread of antimicrobial resistant pathogens, programmes to enhance facility cleaning should be promoted.…”
Section: Discussionmentioning
confidence: 99%
“…4 Controlling COVID-19 requires multidisciplinary input from doctors to cleaners, whose integral role in prevention of spread of disease is often disregarded. 5 A 2015 survey on infection prevention and control (IPC) preparedness of institutions worldwide showed that preparedness levels were only partially adequate. 6 Without appropriate personal protective equipment (PPE), the health workforce is put at risk of infection with COVID-19.…”
Section: Summary Boxmentioning
confidence: 99%
“…Newborns delivered in hospitals in LMICs are 3-20 times more likely to develop an infection compared to those in high-income countries [10]. A critical but often neglected aspect of HAI prevention is basic environmental hygiene, particularly surface cleaning and linen management [11,12]. Systematic removal of microorganisms from hospital surfaces impedes direct bacterial and viral transmission to patients and indirect transmission via the hands of healthcare workers or medical equipment.…”
Section: Introductionmentioning
confidence: 99%